A web questionnaire to determine the advice general practitioners give on probiotics. - Nichols JAA; Grob PR; Roche N (Journal of Nutritional & Environmental Medicine, 2005)
Purpose. To determine what advice general practitioners (GPs) are giving on the health benefits of over-the-counter probiotics. Design. A web-based questionnaire. Materials and methods. The questionnaire was posted on the website for the Southwest Thames Faculty of the Royal College of General Practitioners and letters were sent to all Surrey GPs, inviting them to take part. The questionnaire included a variety of clinical scenarios in which probiotic advice might be appropriate. Results. There was a 16.6% response rate. The value of taking probiotics with and after antibiotics was featured in one question and 72% of GPs were aware that this reduces the incidence of diarrhoea. Thirteen clinical scenarios were included in the questionnaire. Six scenarios involved patients taking antibiotics for various types of infection and seven scenarios described other conditions in which probiotic benefits have been claimed. GPs varied in their experience and opinion as to whether advice to take a probiotic would be appropriate in these scenarios, with the choice of the option 'frequently advise' varying from 63% (recurrent vaginal candidiasis) to 1% (to reduce the risk of bowel and bladder cancer). The first four questions were tested on a sample of 40 non-responders who gave similar responses but a smaller bias in favour of probiotic advice. Conclusions . Although this survey was probably biased in favour of giving probiotic advice, the >50% response to the idea of giving probiotics with at least some clinical scenarios suggests that the idea of advising probiotics, when appropriate, has reached the tipping point in general practice.